Meso-level Model of the Effect of Information and Communication Resources on the Economic Development of Russian Regions - Bartov, Oleg B.; Tretyakova, Elena A. (Economy of Regions, 2021)
The economic problems of the digital age require resolution at all stages, including the meso-level. The article presents results of a study conducted across Russian regions to determine quantitative indicators of the impact of information and communication resources on their economic development. The research aims to assess this effect from the perspective of a systematic approach. To this end, a typology of economic activities is compiled, a meso-level model of influence is developed, then the model is evaluated. A hypothesis concerning the multidirectional effect of external information and communication resources on the gross regional product is advanced and confirmed. From a theoretical perspective, the research takes a spatio-temporal approach derived from the system paradigm. In order to obtain unbiased estimates of the elasticity values, we evaluated the approximation of the meso-level model using the non-regularized least squares method. The results of the study can be used to determine regional strategies for the development of information and communication resources. The significance of the obtained results can be enhanced by increasing the sample size of the official state statistics used as source data. The work concludes by recommending the development and retention of labour resources in the field of information and communication in order to optimise regional economic development by maximising the obtained indicators.